Controlling ionotropic and metabotropic glutamate receptors with light: principles and potential. (February 2015) - Reiner, Andreas; Levitz, Joshua; Isacoff, Ehud Y.
Graphical abstract: Highlights: Tools for manipulating GluRs are needed to decipher signaling at synapses. Optical approaches are non-invasive and provide high spatio-temporal resolution. Photo-pharmacology can be used to manipulate native GluRs. Genetic encoding allows targeting to specific synaptic compartments and cell types. Photoswitchable tethered ligands offer the ultimate precision and specificity. Abstract : Light offers unique advantages for studying and manipulating biomolecules and the cellular processes that they control. Optical control of ionotropic and metabotropic glutamate receptors has garnered significant interest, since these receptors are central to signaling at neuronal synapses and only optical approaches provide the spatial and temporal resolution required to directly probe receptor function in cells and tissue. Following the classical method of glutamate photo-uncaging, recently developed methods have added other forms of remote control, including those with high molecular specificity and genetic targeting. These tools open the door to the direct optical control of synaptic transmission and plasticity, as well as the probing of native receptor function in intact neural circuits.